Two And Three-Point Block Methods For Solving First Order Ordinary Differential Equations In Parallel - Lee, Lai Soon (2000)
This thesis concerns mainly in deriving new 2-point and 3-point block methods for solving a single equation of first order ODE directly using constant step size in both explicit and implicit methods. These methods, which calculate the numerical solution at more than one point simultaneously, are suitable for parallel implementations.The programs of the methods employed are run on a shared memory Sequent Symmetry SE30 parallel computer. The numerical results show that the new methods reduce the total number of steps and execution time.The accuracy of the parallel block and I-point methods is comparable particularly when finer step size are used.The stability of the new methods also had been investigated.